Bactericidal activity of propylene glycol, glycerine, polyethylene glycol 400, and polyethylene glycol 1000 against selected microorganisms - Nalawade, Triveni Mohan (J Int Soc Prev Community Dent, 2015)
AIM: The aim of the present study was to evaluate the bactericidal activity of propylene glycol, glycerine, polyethylene glycol 400 (PEG 400), and polyethylene glycol 1000 (PEG 1000) against selected microorganisms in vitro. MATERIALS AND METHODS: Five vehicles, namely propylene glycol, glycerine, PEG 400, PEG 1000, and combination of propylene glycol with PEG 400, were tested for their bactericidal activity. The minimum bactericidal concentration was noted against four standard strains of organisms, i.e. Streptococcus mutans American Type Culture Collection (ATCC) 25175, Streptococcus mutans ATCC 12598, Enterococcus faecalis ATCC 35550, and Escherichia coli ATCC 25922, using broth dilution assay. Successful endodontic therapy depends upon thorough disinfection of root canals. In some refractory cases, routine endodontic therapy is not sufficient, so intracanal medicaments are used for proper disinfection of canals. Intracanal medicaments are dispensed with vehicles which aid in increased diffusion through the dentinal tubules and improve their efficacy. Among the various vehicles used, glycerine is easily available, whereas others like propylene glycol and polyethylene glycol have to be procured from appropriate sources. Also, these vehicles, being viscous, aid in sustained release of the medicaments and improve their handling properties. The most commonly used intracanal medicaments like calcium hydroxide are ineffective on many microorganisms, while most of the other medicaments like MTAD (Mixture of Tetracycline, an Acid, and a Detergent) and Triple Antibiotic Paste (TAP) consist of antibiotics which can lead to development of antibiotic resistance among microorganisms. Thus, in order to use safer and equally effective intracanal medicaments, newer alternatives like chlorhexidine gluconate, ozonized water, etc., are being explored. Similarly, the five vehicles mentioned above are being tested for their antimicrobial activity in this study. RESULTS: All vehicles exhibited bactericidal activity at 100% concentration. CONCLUSION: Propylene glycol was effective against three organisms namely S. mutans E. faecalis and E. coli and its bactericidal activity was at 50%, 25% and 50% respectively. PEG 1000 was effective against S. mutans and E. coli at 25%. Hence propylene glycol was effective on more number of organisms of which E. faecalis is a known resistant species. PEG 1000 was bactericidal at a lower concentration but was effective on two organisms only.